3+(4/6)x=(4/6)x+9

Simple and best practice solution for 3+(4/6)x=(4/6)x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+(4/6)x=(4/6)x+9 equation:



3+(4/6)x=(4/6)x+9
We move all terms to the left:
3+(4/6)x-((4/6)x+9)=0
Domain of the equation: 6)x!=0
x!=0/1
x!=0
x∈R
Domain of the equation: 6)x+9)!=0
x!=0/1
x!=0
x∈R
We add all the numbers together, and all the variables
(+4/6)x-((+4/6)x+9)+3=0
We multiply parentheses
4x^2-((+4/6)x+9)+3=0
We multiply all the terms by the denominator
4x^2*6)x+9)-((+3*6)x+9)+4=0
We add all the numbers together, and all the variables
4x^2*6)x+9)-(18x+9)+4=0
Wy multiply elements
24x^3=0
We do not support expression: x^3

See similar equations:

| -2(x-6)=-3(x-7)-2x | | 0.2p+1.5=6.5 | | -765=15v | | 2/7=x10/ | | 2−c=−10−3c,c= | | u/17=-7 | | 6x^2=36x-150 | | 3p=18p= | | 5x=5,330 | | 5g-1/3=-10/3 | | 1.1+0.25x=0.85+0.3x | | 3(2r+7)-5r=3-6(-3+4r) | | s-21=313 | | 0.02x+0.7=0.8+-0.03x | | 6x-15+2x=177 | | 0.02(y-2)+0.10y=0.047-0.2 | | 90=v+v | | -3v+8(v-6)=-33 | | -4,863+81.1m=-3,645+76.9m | | 5x+27=62 | | 8x-20+5x+37=180 | | z+20=67 | | 1/3x-5+2/3x=10 | | 10x-5=35x | | 3y+10(y-1.5)=24 | | 5x-2=228 | | F=Px(1+0.05)4 | | 10x+5=85° | | 55=q+32 | | 12+35+x=180 | | -6=2(y+5)+6y | | -8=-4+m/4 |

Equations solver categories